Pilot Comparison of Adjustment Protocols of Personal Sound Amplification Products - Reed, Nicholas S.; Oliver, Antoinette; Srinivasan, Nirmal Kumar; Lin, Frank R.; Korczak, Peggy A. (Seminars in Hearing, 2019)
The Over-the-Counter Hearing Aid Act of 2017 was signed into law in August 2017 and facilitates the introduction of direct-to-consumer sales of hearing aids for adults with mild-to-moderate hearing loss. Among many questions surrounding over-the-counter sales is the ability of users to self-fit amplification. Many studies have conducted self-fitting procedures using guidance materials provided by audiologists. In this pilot, we explore the ability of users to self-adjust personal sound amplification devices using only materials provided by the manufacturer and contrast this with models that involve a hearing professional. Outcomes to assess adjustments included clinic-based speech-in-noise measures and ability to approximate NAL-NL2 prescriptive targets. We found that an audiologist-driven model provided the best outcomes. However, it is unknown if the difference is clinically meaningful.
Keywords: Personal Sound Amplification Product; over-the-counter device; self-fit amplification; direct-to-consumer sales